Did Gandhi Never Exist? or: Can You Defend Yourself to Death? - Doepp, Manfred (European Journal of Applied Sciences, 2025)
War has become acceptable again. People are talking about it as a different form of politics, as if the wars of the past decades had not brought death and misery to many populations. And as if a nuclear war would not mean the annihilation of entire peoples. This is based on a friend-enemy mentality. Alongside Jesus the Christ, it was above all Mahatma Gandhi who contradicted this. He not only called for non-violent resistance, but was also successful in South Africa and India. Passive social resistance can checkmate an aggressor or dominator, as this implies cultural superiority. If we want to maintain our civilizational status, we urgently need to return to Gandhi.